Homosexuality, a European Community issue : essays on lesbian and gay rights in European law and policy - Waaldijk, Kees; Clapham, Andrew (Dordrecht : Martinus Nijhoff, 1993)
Fonds Suzan Daniel (FSD)
Engels
Monografie